DESKRIPSI KOMPETENSI GURU SMP MATA PELAJARAN MATEMATIKA DAN IPA - Titin, Titin (Universitas Tanjungpura, 2015)
This research aimed to describe the competency of junior high school teachers of Mathematics and Science subjects. This research uses descriptive method with the survey method. The data source in this researchÂ is junior high school teachers of Mathematics and Science subjects which are incorporated in MGMP Sub Rayon 03 Samalantan, the number of teacher is 20. The data were collected through questionnaires. To find out the description of the competence of teachers it used descriptive analysis by using percentage. The result showed an overall competence of teachers are in a good category. The sequentially percentage of the competency of teachers are pedagogic (72.25%), professional competence (83.00%), personal competence (85.00%) and social competence (77%). Key word : Competence, Junior High School Teachers.